Metabolic activity of an anammox population affected by major environmental factors - Rao Yifu; Meng Jia; Tian Yajie; Li Jianzheng (E3S Web of Conferences, 2021)
Anammox is known as a cost-effective approach to nitrogen removal from ammonium-rich wastewater. However, the eco-physiological characteristics of anammox population have not well been understood so far, which has obstructed the practical application of anammox process. In the present research work, an enrichment culture of anammox population was collected from an expanded granular sludge bed (EGSB) reactor, and the anammox activity was evaluated by various pH, temperature and reactant density, progressively. The results showed that the optimal ecological amplitude of pH and temperature for the anammox population was ranged from 7.0-7.5 and 30°C-35°C, respectively. To make anammox process more efficient, the density of NH4+-N and NO2−-N should be around 10.0 and 4.0 mmol·L−1, respectively. It was found that anammox population was more sensitive to NO2−-N density than NH4+-N density, and then NO2−-N density was proposed as a key indicator to practicing anammox process in engineering. With the findings, the present research will be significant in practicing annamox process.